Time to change? Present and prospects of hemorrhoidal classification - Wang, Ling; Ni, Jiachun; Hou, Changcheng; Wu, Di; Sun, Li; Jiang, Qiong; Cai, Zengjin; Fan, Wenbin (Frontiers in Medicine, 2023)
As a common benign anal condition, the high incidence and recurrence of hemorrhoids pose challenges for both patients and doctors. The classification of hemorrhoids plays a crucial role in assessing, diagnosing, and treating the condition. By using appropriate classification and corresponding treatment strategies, we can achieve higher cure rates and lower recurrence rates of hemorrhoids. Since the introduction of the Miles classification in 1919, various classifications have been developed, which include objective classifications based on anatomical or instrumental assessment and subjective classifications based on symptoms and patient sensations. These classifications aim to accurately evaluate the condition. In this study, we discuss the evaluation values of each classification in terms of their advantages, disadvantages, treatment relevance, reproducibility, practicality, and assessment value. We also analyze the significant and essential factors, principles of use, and components of assessment indicators of hemorrhoidal classification. This study proposes several strategies to address the limitations of current hemorrhoidal assessment methods. All these will provide a reference for the development regarding the assessment and classification of hemorrhoids and clinical diagnosis and management of hemorrhoids.